Mesenchymal Stem Cells in a Polycaprolactone Conduit Promote Sciatic Nerve Regeneration and Sensory Neuron Survival after Nerve Injury - Frattini, Flávia (2012)
Texto completo: acesso restrito. p. 2030-2039